2021
DOI: 10.1249/01.mss.0000764536.12942.8d
|View full text |Cite
|
Sign up to set email alerts
|

Exercise As A Treatment For Non-alcoholic Fatty Liver Disease: A Meta-Review

Abstract: To examine the effect of exercise on NAFLD biomarkers including aspartate transaminase (AST), alanine transaminase (ALT), and gamma-glutamyl transferase (GGT); triglycerides (TG), low-density lipoprotein (LDL), and high-density lipoprotein (HDL); and glucose (GLU) and insulin (INS). METHODS: We searched five electronic databases to identify randomized controlled trials that: 1) included adults with NAFLD; 2) had an aerobic (AE) and resistance (RE) exercise intervention alone or combined (CE) without dietary or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…There are no specific drugs or treatment for fatty liver at this time. According to numerous references, fatty liver can be reversed, especially when the patients adhere to a proper exercise program, dietary recommendations, and/or appropriate medications [ 1 ]. It has been reported that adopting exercise therapy in an effort to ultimately stop medication may be a more scientific and ideal way to treat fatty liver [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…There are no specific drugs or treatment for fatty liver at this time. According to numerous references, fatty liver can be reversed, especially when the patients adhere to a proper exercise program, dietary recommendations, and/or appropriate medications [ 1 ]. It has been reported that adopting exercise therapy in an effort to ultimately stop medication may be a more scientific and ideal way to treat fatty liver [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%